Effects of nitrogen reduction and aged biochar on soil properties, root characteristics and ascorbic acid glutathione cycle of dryland maize - Sun, Chen; Ji, Wenhui; Liu, Jian; Wang, Jianhua; Hu, Shuping; Zhou, Jun; Liu, Ruifang; Li, Yan; Du, Jiang; Cao, Guohui; Wang, Zhaoran; Sun, Jiying (Frontiers in Plant Science, 2025)
IntroductionNitrogen (N) and Biochar (B) are well-documented in plant and soil improvement, but their regulatory role in mitigating plant oxidative stress under dryland cultivation is poorly understood. The current study was conducted to investigate the effect of nitrogen reduction and aged biochar on soil texture, root characteristics, antioxidants activities, and yield of maize under dryland cultivation.MethodsA split plot design was employed in the field experiments, incorporating three nitrogen levels (N0:0, N150:150 and N300:300 kg N•ha-1) and four biochar application rates (B0:0, B8:8, B16:16 and B24:24 t•ha⁻¹).ResultsThe soil bulk density (SBD) under B24 decreased by 11.07%, however, the soil porosity (SP) increased by 15.11% as compared to B0. The activities of N-acetyl-β-D-glucosaminidase (NAG) and leucine aminopeptidase (LAP) under N150 treatment increased by 42.82% and 17.20% as compared to N300. B8, B16, and B24 treatment significantly increased total root length (TRL) and total root surface area (TRSA) by 5.72-18.65% and 19.12-38.56%, as compared to B0. Maize experienced less oxidative stress under N150 treatment due to the lower accumulation of superoxide radical (O2-) by 38.32%, and hydrogen peroxide (H2O2) by 19.25% as compared to N300 treatment. The addition of 24 t•ha-1 biochar reduced the levels of O2- and H2O2 by increasing the activities of superoxide dismutase (SOD) by 13.64%, ascorbate peroxidase (APX) 11.86%, monodehydroascorbate reductase (MDHAR) 13.13%, dehydroascorbic reductase (DHAR) 11.50%, and glutathione reductase (GR) 9.82% compared to B0.DiscussionThe results revealed that nitrogen reduction and aged biochar could alleviate the harmful effects of drought stress by improving soil quality, root characteristics, and the enzyme activities in ascorbic acid glutathione (AsA–GSH) cycle of maize which indicate that the nitrogen reduction and aged biochar application might be a sustainable strategy to enhance maize growth under dryland cultivation.